Attitude and Knowledge of Participating Couples Towards the Premarital Hemoglobinopathy Screening Program in Duhok–Iraq. - Rebeen Abdulsalam Mohammed Sediq; Salar Ayoub Sulaiman; Nasir Al-Allawi (Advanced Medical Journal)
Background and Objectives: The premarital screening program for hemoglobinopathies was initiated in the Kurdistan region nearly 15 years ago. In the current study we aimed to assess the attitude and knowledge of the targeted couples, since these are among the main determinants of its success.